Anime as Social Imagination: Media Infrastructure and Enactive Cognition in "Code Geass" and "Penguindrum" - Hack, Brett (Cinema: Journal of Philosophy and the Moving Image, 2024)
Anime has been recognized as a distinct mode of image-thinking that can inform philosophical inquiry. In particular, anime has provided philosophies of media with new insights on how to reconceptualize subjectivity and collectivity within our contemporary media-worlds. This essay aims to contribute to this project by examining how anime’s media-form interacts with the shared cognitive processes of human imagination that are actualized within anime’s fictions. Analysis will describe anime’s image-creation processes as techniques of imagination, that is, as material and cognitive “strategies and devices” that make complex, non-present objects “perceivable and experienceable,” and so enable collective practices of speculation (Heise, 2008, p. 67). The essay elaborates these techniques as an “enactive” mode of social imagination, a collaborative process of sense-making through which creators and viewers feel through the contours of contemporary social imaginaries and explore conditions of possibility for changing them (Gallagher, 2017). The theoretical and political implications of this view will be examined through a comparative analysis of two original series from the high period of neoliberal hegemony in Japan: Code Geass: Lelouch of the Rebellion (Taniguchi, 2006-2008) and Penguindrum (Ikuhara, 2011). These very different series similarly use anime techniques of imagination to experientially navigate what Thomas Lamarre (2018, p. 29) calls the media “infrastructure complex” of early 21st-century Japan. The two series’ fantasies of changing the world within this context become perceivable through anime’s multivalent processes of social imagination, which move from the fictional enactments themselves and out into broader projects of re-imagining real-world social relations. The essay will ultimately argue that anime’s social imagination offers a way to philosophically and critically mobilize the enduring role of fictional experience and its forms of agency as tools for negotiating between different layers and conceptualizations of media-experience and their political enunciation.